2021
DOI: 10.1038/s41388-021-02094-9
|View full text |Cite|
|
Sign up to set email alerts
|

A dimerization-dependent mechanism regulates enzymatic activation and nuclear entry of PLK1

Abstract: Polo-like kinase 1 (PLK1) is a crucial regulator of cell cycle progression. It is established that the activation of PLK1 depends on the coordinated action of Aurora-A and Bora. Nevertheless, very little is known about the spatiotemporal regulation of PLK1 during G2, specifically, the mechanisms that keep cytoplasmic PLK1 inactive until shortly before mitosis onset. Here, we describe PLK1 dimerization as a new mechanism that controls PLK1 activation. During the early G2 phase, Bora supports transient PLK1 dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
2
9
0
1
Order By: Relevance
“…Very recent data also suggest transient dimerization of PLK1 as a new mechanism underlying the activation of cytoplasmic PLK1 during G2 phase ( 23 ). These data suggest that in early G2 phase Bora facilitates PLK1 dimerization, acting as an allosteric modulator of the PLK1, that shifts from dimeric to monomeric active state; in late G2, PLK1 Thr210 phosphorylation by Aurora kinase A triggers dimer dissociation and the PLK1 monomers generated foster mitotic entry.…”
Section: Structure and Regulation Of Plk1mentioning
confidence: 99%
“…Very recent data also suggest transient dimerization of PLK1 as a new mechanism underlying the activation of cytoplasmic PLK1 during G2 phase ( 23 ). These data suggest that in early G2 phase Bora facilitates PLK1 dimerization, acting as an allosteric modulator of the PLK1, that shifts from dimeric to monomeric active state; in late G2, PLK1 Thr210 phosphorylation by Aurora kinase A triggers dimer dissociation and the PLK1 monomers generated foster mitotic entry.…”
Section: Structure and Regulation Of Plk1mentioning
confidence: 99%
“…18,29,30 These observations are also consistent with a proposed model whereby dimeric PLK1 bound by Bora remains in an inactive conformation until G2, when phosphorylation of PLK1 at T210 releases monomeric PLK1 for entry into the nucleus. 16 In untreated asynchronous PC3 cells, approximately one-fifth of the cells are in G2 or mitosis as measured by flow cytometry; 19 thus, only a small fraction of the asynchronous population are in G2 when analyzed by CETSA, the point at which PLK1 is proposed to be in an active, monomeric form that enters the nucleus. The fact that soluble PLK1 levels were decreased by 80% yet not completely lost in mitotic cells after BI treatment rules out explanations besides thermal stability for the loss of soluble PLK1, as a nonthermal mechanism would be expected to occur to the same extent in protein samples from asynchronous and mitotic cells treated identically.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Raab et al performed elegant experiments with chromosomally integrated (nonectopically expressed) PLK1 to demonstrate that Bora transiently promotes PLK1 dimerization early in G2, whereas T210 phosphorylation by Aurora-A initiates dissociation of the dimer. 16 The interactions between PBD and KD are implicated in a mechanism of autoinhibition of PLK1 that produces a closed/ inactive conformation. Phosphorylation at T210 or Ser137 of PLK1 by Aurora-A in coordination with its partners disrupts the intramolecular interactions between the PBD and KD, resulting in an opened/active conformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In case of insufficient FAK signaling due to downregulated protein expression or cell detachment, cells often form a monopolar spindle and exhibit a strongly delayed mitotic exit ( Kamranvar S A et al, 2022a ). PLK1 activity is known to be controlled by phosphorylation at Thr210 in the activation loop by Aurora A ( Gheghiani L et al, 2017 ; Raab M et al, 2022 ), and additional PLK1 modifications have been reported, which may further contribute to its spatiotemporal regulation ( Caron D et al, 2016 ; Liu X et al, 2016 ; Yang X et al, 2017 ). Also, the regulation of Aurora A is complex, and several different activation mechanisms have been elucidated ( Zhao Z S et al, 2005 ; Tavernier N et al, 2021 ).…”
Section: Spindle Formationmentioning
confidence: 99%